ID: 54. Issue 1 (November 2015) - Wienerroither, Sebastian; Shukla, Priyank; Farlik, Matthias; Majoros, Andrea; Vogl, Claus; Cheon, HyenJoo; Stark, George; Strobl, Birgit; Müller, Mathias; Decker, Thomas
<x xml:space="preserve">Abstract</x> Infection of macrophages with the bacterium Listeria monocytogenes (Lm) stimulates NFkB signalling and the synthesis of type I Interferons (IFN-I). As a secondary response IFN-I signal through the type I IFN receptor (IFNAR) to activate the ISGF3 complex containing STAT1, STAT2 and IRF9 subunits. Using ChIP-Seq we provide a genome-wide analysis of genes with binding sites for both NFkB and the IFN-I activated STATs. In particular we define the group of genes displaying synergistic activation by STAT and NFkB pathways. This group includes the Nos2 gene encoding inducible nitric oxide synthase. Detailed analysis of this gene provides a mechanistic explanation how STAT and NFkB pathways cooperate in promoter activation, i.e. the establishment of activating histone marks and the recruitment and phosphorylation of RNA polymerase II. In particular we demonstrate a signal integrator function for the mediator complex. In summary our data explain the functional interplay between two major antimicrobial pathways.